2018
DOI: 10.3389/fmars.2018.00142
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on the Great Amazon Reef: Extension, Biodiversity, and Threats

Abstract: Here we provide a broad overview of the Great Amazon Reef System (GARS) based on the first-ever video surveys of the region. This footage supports four major hypotheses: (1) the GARS area may be six times larger than previously suggested (up to 56,000 km 2 ); (2) the GARS may extend deeper than previously suggested (up to 220 m); (3) the GARS is composed of a greater complexity and diversity of habitats than previously recognized (e.g., reef platforms, reef walls, rhodolith beds, and sponge bottoms); and (4) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
101
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(110 citation statements)
references
References 25 publications
0
101
0
9
Order By: Relevance
“…Francini‐Filho et al. () suggested that these MEs comprise a significant diversity of environments, including rhodolith beds, sponge grounds and reef structures, such as biogenic walls and platforms.…”
Section: Recent Advances In Knowledge About the South Atlantic Mesmentioning
confidence: 99%
See 2 more Smart Citations
“…Francini‐Filho et al. () suggested that these MEs comprise a significant diversity of environments, including rhodolith beds, sponge grounds and reef structures, such as biogenic walls and platforms.…”
Section: Recent Advances In Knowledge About the South Atlantic Mesmentioning
confidence: 99%
“…These Amazonian MEs (the Great Amazon Reef sensu Francini‐Filho et al., ) are distributed across a large area (56,000 km²) of the North Brazil Shelf, between the shelf‐edge and the upper slope (70–220 m depth; Francini‐Filho et al., ). Despite the variability of seascapes, this ecosystem has a clear bathymetric gradient: Rhodolith beds and algal frameworks dominate the shallowest sector (70–180 m), but in the deepest sector (180–220 m), marine animal forests (composed of black corals, barrel sponges and octocorals) and associated fishes (e.g., butterflyfish) are more common.…”
Section: Recent Advances In Knowledge About the South Atlantic Mesmentioning
confidence: 99%
See 1 more Smart Citation
“…These geologically similar margins comprise large accumulations of oil with high commercial value (Milani et al, 2001). More than a hundred exploratory blocks have been auctioned by Brazil since 2012, but environmental licensing is still a matter of discussion and concern (e.g., Francini-Filho et al, 2018), largely due to the recently mapped reef system off the Amazon mouth (Cordeiro et al, 2015;Moura et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Considering the expansion of the oil and gas industry in the ACM, the occurrence of mesophotic reefs along the shelf and shelf break (Moura et al, 2016), and even the overestimated size of the "Great Amazon reefs" by Francini-Filho et al (2018), a quantitative terrain characterization is a powerful tool to map potential benthic habitats based on their morphology (Lecours et al, 2016) and to set the stage for marine spatial planning (e.g., Moura et al, 2013). Herein, a quantitative terrain characterization is used to map potential benthic habitats based on their morphology.…”
Section: Introductionmentioning
confidence: 99%